PENGARUH VARIASI PENAMBAHAN EKSTRAK DAUN KELOR (MORINGA OLEIFERA) TERHADAP WARNA DAN ORGANOLEPTIK SELAI BUAH NAGA MERAH (HYLOCEREUS POLYRHIZUS) - Ihlana Nairfana (Faculty of Agricultural Technology, 2020)
Red dragon fruit is one type of tropical fruit containing vitamin C, vitamin E, vitamin A, and polyphenol compounds which have the potential as antioxidants, and have high fiber. The high water content in red dragon fruit results in red dragon fruit being easily damaged. One of the processed products of red dragon fruit is jam. Red dragon fruit jam products are generally known to have high levels of antioxidants and vitamin C, but on the other hand do not contain much protein, it is known that the protein in dragon fruit is only 0.53 grams per 100 grams, on the other hand Moringa leaves contain 6.7 grams of protein per 100 grams. Therefore, the addition of Moringa leaf extract allows can add protein and other nutrients to the red dragon fruit jam. Moringa oleifera plant has many benefits and very high nutritional content, Moringa leaves contain vitamin A, vitamin B, vitamin C, calcium, potassium, iron and protein in very high amounts that are easily digested by the human body. The purpose of this study was to determine the effect of the addition of Moringa oleifera leaf extracts to the physical color and organoleptic quality of the hedonic red dragon fruit jam (Hylocereus polyrhizus). This study uses a Completely Randomized Design (CRD), the factor used is the concentration of Moringa leaf extract (P1 = 0%, P2 = 5%, P3 = 10%, P4 = 15%). Data analysis using ANOVA with a significance level of 5%. Based on the results of the study obtained differences in the concentration of Moringa leaf extract affect the brightness of the color of red dragon fruit jam, the higher the concentration of Moringa leaf extract added in making dragon fruit jam, the color will be darker. In the organoleptic test results showed that differences in the concentration of Moringa leaf extract affect the level of taste preferences, but does not affect the level of texture, color, and aroma of red dragon fruit jam.